Comparison of Turkey and Bulgaria's Health Systems - Rujnan Tuna (Association of Nurse Managers, 2021)
The health system as a whole consists of inputs, processes, outputs and result elements that are contained within all kinds of services in order to improve health. Today, countries have developed different health systems in order to control the health expenditures while maintaining the effectiveness of health systems. The aim of this study was to compare the infrastructure of health systems in Turkey and Bulgaria. Population of Bulgaria is much younger compared to Turkey's population. However, although higher number of hospitals are located in Turkey; the number of hospital beds per person and the proportion of healthcare workers are lower than that of Bulgaria. It was also observed that the aim is to ensure a state guarantee to all citizens within the scope of health services in Turkey. However, in Bulgaria, it was observed that low income citizens were excluded from these services by individual health contracts. While the provision of health services in Turkey is carried out under state responsibility, in Bulgaria provision of health services is not under state responsibility but these services are purchased with premiums paid by individuals.